Synthesis of sulfonamides incorporating piperazinyl-ureido moieties and their carbonic anhydrase I, II, IX and XII inhibitory activity. Issue 18 (15th September 2015) - Congiu, Cenzo; Onnis, Valentina; Deplano, Alessandro; Balboni, Gianfranco; Dedeoglu, Nurcan; Supuran, Claudiu T.
Graphical abstract K I (hCA I) = 7.5–9490 nM; KI (hCA II) = 0.75–721 nM; KI (hCA IX) = 8.7–517 nM; KI (hCA XII) = 17.0–179 nM.